BONES IN A CITY. THE BONE ARTIFACTS FROM NAPOCA AND ITS CLOSE CATCHMENT AREA - Lóránt Vass; Sorin Cociș (Journal of Ancient History and Archaeology)
Many aspects of the topography and history of the Roman city of Napoca are still unknown despite the intensive rescue excavations in the recent years which is partially due to the challenges of urban archaeology in a continuously inhabited settlement. The small finds recovered from these archaeological investigations are usually not published, except for some special type of artefacts (pottery, coins, brooches etc.), thus hardly any aspects of the local economy and handicraft are known. The systematic analysis of eighty-six bone objects recovered from mostly recent excavations carried at four topographical points (Victor Deleu Street no. 1, Museum Square no. 2 – from the densely inhabited intra muros area; Avram Iancu Street 21-23 – southern cemetery of the Roman city, and the villa rustica from the Lombului Hill, outside but still in the territorium of the city) endeavours to complete this lack. The not so numerous bone items seem at the first glance very standardized, simple, and unspectacular, however due to the well-dated and documented find contexts they offer an insight into the bone industry and craftmanship in Napoca and in the Dacian provinces. Compared to other Dacian (urban) settlements the objects are very simple and “common”, and this simplicity and uniform character of the finds is what make this lot very interesting and intriguing.